Learning English Speaking Skill in The Field of Tourism with The Blended Culture Model - Kristiana, Vera (IKIP Siliwangi, 2025)
This blended culture-based English language learning model needs to be implemented. The activity of English language learning teaches mostly western cultures compared to local culture. This problem is exacerbated by technological advances in the form of electronic media and print media, television as learning resources that can be accessed freely by students. The objective of the research was to know influence from blended culture to English speaking skills, especially in the tourism sector. The data was found out using instruments such as tests, questionnaires and interviews as an effort to find out how to implement the blended culture-based English language learning model. The study used a pre-experimental design. The design was a pre-experimental design caused it was not yet a pure experiment and also caused there were still external variables that affected the dependent variable. The research was One-Group Pretest-Posttest Design. In this design there was a pretest before treatment was given. In this study, the results of the treatment could be seen more accurately, because it could be compared with the situation before and after the treatment.